2018
DOI: 10.1159/000490076
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin Attenuates Inflammatory Pain by Inhibiting Microglial Activation and Akt-NF-κB Signaling in the Central Nervous System

Abstract: Background/Aims: Paeoniflorin (PF) is known to have anti-inflammatory and paregoric effects, but the mechanism underlying its analgesic effect remains unclear. The aim of this study was to clarify the effect of PF on Freund’s complete adjuvant (CFA)-induced inflammatory pain and explore the underlying molecular mechanism. Methods: An inflammatory pain model was established by intraplantar injection of CFA in C57BL/6J mice. After intrathecal injection of PF daily for 8 consecutive days, thermal and mechanical w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 37 publications
(35 reference statements)
1
24
0
1
Order By: Relevance
“…As one of the active chemical compounds extracted from the roots of Paeonia lactiflora , PF has been reported to possess the analgesic activity against inflammatory pain 12,14 . It was worth noting that PF curbed NLRP3 inflammasome activation in Mϕs recruited into the inflamed skin tissues (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the active chemical compounds extracted from the roots of Paeonia lactiflora , PF has been reported to possess the analgesic activity against inflammatory pain 12,14 . It was worth noting that PF curbed NLRP3 inflammasome activation in Mϕs recruited into the inflamed skin tissues (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cinnamomum cassia Presl, a constitutive agent in GBH, has been shown to exhibit anti-inflammatory effects in murine BV2 microglia cells, and Paeonia suffruticosa Andrews, another element of GBH, has been reported to induce antioxidative stress effects in rat pheochromocytoma PC-12 cells [14, 15]. Moreover, amygdalin, a component of Prunus persica Batsch, induces neurotrophic effects via the activation of the extracellular signal-regulated kinase (ERK)1/2 pathway in PC12 cells [16], paeoniflorin, a component of Paeonia suffruticosa Andrews and Paeonia lactiflora Pallas, reduces proinflammatory cytokines in CNS via the activation of Akt-NF- κ B signaling pathway in vivo and in vitro [17], and cinnamic acid, a component of Cinnamomum cassia Presl, upregulates the expression of SOCS3 in glial cells via the CREB pathway [18].…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] A recent study reported that paeoniflorin, obtained from P. lactiflora can mitigate inflammatory pain by suppressing Akt-NF-kB pathway. [ 10 ] C. myrrha , a native plant to Northeastern Africa, has been used to treat rheumatoid arthritis, sinusitis, and other illnesses. [ 11 ] Both C. myrrha and P. lactiflora have been historically used as natural antinociceptives since ancient times, and both have proven functions against peripheral and central pains.…”
Section: Discussionmentioning
confidence: 99%